Architect Janko Šafarik and his Opus in Belgrade (1911-1932) - Bankovic, Angelina (Arhitektura i urbanizam, 2023)
The subject of the research presented in this paper is the Belgrade opus of architect Janko Šafarik (1882–1949). The research is mainly based on primary sources preserved in the Historical Archives of Belgrade, the Belgrade City Museum, the Military Archives and the archives of the Technical University in Dresden. Although Šafarik and his architectural opus have not been completely presented in any previously published papers, a number of them contain important data related to his work, which is why they were considered in this research. The architect’s biographical information is presented, followed by his Belgrade opus, which is chronologically divided into before and after World War One. Most attention is devoted to the most fruitful period of his activity, the 1930s. That is when Šafarik worked in the Technical Bureau - the Fenix Company, within which most of his projects were created. All projects attributed to Šafarik, confirmed by considering available archival material, are presented in this paper, regardless of whether they were carried out or not. Through their analysis, the conclusion was reached that Šafarik did not belong to a group of architects who were looking for their own unique architectural expression, or to those who were dominantly committed to one style, but rather that in his oeuvre, his approache varied, mostly in accordance with the dominant approach at the time each individual project was created.